2023
DOI: 10.1021/acs.jpcc.2c07925
|View full text |Cite
|
Sign up to set email alerts
|

Near- and Far-Field Optical Properties of Dipole-Multipole Plasmonic Coupled Building Blocks

Abstract: The plasmonic hybridization in the complex nanostructure innovates multiple fields, such as chemistry, physics, materials science, and biology. In this article, we systematically studied the near- and far-field optical properties of building blocks of coupled dipoles or coupled dipoles and multipoles or a multipole in a coupled plasmonic system through numerical simulations. To be specific, the far-field spectrum, near-field phase changes, and angular radiation patterns of plasmonic hybridized structures were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…36 Recently, some theoretical studies have shown that plasmonic hybridization between a dipolar mode and a multipolar mode showed more dramatic optical response in terms of near- and far-field than that among dipolar modes, which may lead to the improvement of photothermal applications. 37…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Recently, some theoretical studies have shown that plasmonic hybridization between a dipolar mode and a multipolar mode showed more dramatic optical response in terms of near- and far-field than that among dipolar modes, which may lead to the improvement of photothermal applications. 37…”
Section: Introductionmentioning
confidence: 99%
“…36 Recently, some theoretical studies have shown that plasmonic hybridization between a dipolar mode and a multipolar mode showed more dramatic optical response in terms of near-and far-field than that among dipolar modes, which may lead to the improvement of photothermal applications. 37 In this study, we investigated the dipole-multipole (D-M) plasmonic coupling between a TiN NP's dipolar mode (B750 nm) and an Au NR's multipolar mode (B750 nm), which was compared to the dipole-dipole (D-D) plasmonic coupling among TiN NPs' dipolar modes. First, we fabricated Au NR/TiN NP/PVDF nanofilms and neat TiN NP/PVDF nanofilms, which contain D-M coupled Au NR/TiN NP nanoclusters and D-D coupled TiN NP nanoclusters, respectively.…”
Section: Introductionmentioning
confidence: 99%